Payment of Compensation for Officials Who Did Not Implement the Decision of the State Administrative Court - Aries Saputro (Yuridika, 2019)
Unlawful Acts by the Agency and/or Government Official (onrechtmatige overheidsdaad) carried out in exercising their authority, which may result in the public, individuals and private legal entities to bring a civil suit to the District Court, to obtain compensation. Meanwhile, the public, individuals or legal entities may request an administrative claim for the issuance of a State Administration Decree by a Government Official to the State Administrative Court. The Court's Decision is a representation of legal considerations by the Judge which is recognized as "res judicata pro veritate habetur" which means that the judge's decision is considered to be correct and immediate. In the District Court District for Officers who do not implement the Decision, an execution will be carried out, if there is an execution from the court in this case, it is due to the trial that the implementation of the Decision is carried out in its leadership capacity in the PTUN Decision Domain, in the civil domain in the Court. If the Government Official sued loses, compensation must go through the Government Budget for the Community, Individuals and Legal Entities and vice versa. However, the Government Officials specifically against the PTUN Decision won back sometimes when they were not ready to implement the Court's Decision as it was done by force. Because the efforts carried out are contained within, as is the case, the decision cannot be carried out and handled by the law contained therein.